Factor V-Leiden Mutation: A Common Risk Factor for Venous Thrombosis among Lebanese Patients. (12th June 2012) - Kreidy, Raghid
Abstract : Aim . Lebanon exhibits one of the highest prevalences of factor V-Leiden (FVL) in the world (14.4%). The aim of this study is to evaluate the incidence of FVL mutation among Lebanese patients with lower extremity venous thrombosis. Material and Methods . From January 2003 to January 2011, 283 consecutive Lebanese patients, diagnosed with deep venous thrombosis (DVT) by duplex scan, were retrospectively reviewed. FVL mutation was tested among patients with conditions highly suggestive of hypercoagulation states (65 patients). Results . FVL mutation was detected among 56.9% of patients, 68.6% of patients younger than 50 years, and 43.4% of patients older than 50 years (P = 0.041 ). FVL mutation was commonly reported in young adults, in patients with pregnancy, estrogen drugs, recurrent DVT, and resistance to anticoagulation. Conclusion . The high rate of FVL mutation observed among Lebanese patients with venous thrombosis is related to the high prevalence of this mutation in the Lebanese population. Thrombophilia screening should be tailored to accommodate a population's risk factor. In countries with high prevalence of FVL, this mutation should be screened among patients younger than 50 years and patients with situations highly suggestive of hypercoagulation states.